UMP-MOHE Outreach Programme for single mothers with Pineapple Mushroom Innovation - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 30 October 2022 - The Pineapple Mushroom Innovation Project introduced by Universiti Malaysia Pahang (UMP) lecturer, Associate Professor Dr. Aizi Nor Mazila Ramli, who is the Deputy Director, Research Management Centre, Research and Innovation Department, was able to transfer the pineapple mushroom cultivation technology using pineapple waste to the target community.